8.5k views
3 votes
Please Please Please help! 

If you were to use the substitution method to solve the following system, choose the new equation after the expression equivalent to x from the first equation is substituted into the second equation.

−x + 5y = 1
2x + 4y = −4



answers

1. 2(5y − 1) + 4y = −4

2. 2(−5y + 1) + 4y = −4

3. 2x + 4(−5y + 1) = −4

4. 2x + 4(5y − 1) = −4

User GingerJim
by
5.9k points

1 Answer

5 votes
take the first equation and set it to equal x by subtracting 5y from both sides and multiplying by -1. Looks like this...

-x + 5y = 1
-5y -5y
-x = -5y + 1
-1(-x = -5y + 1)
x = 5y - 1 ... substitute this into the second equation you get.....

2(5y - 1) + 4y = -4 answer is #2
User Vero
by
5.7k points